Optimization of solid oxide cells short stack with large area cells - Lim, Kok Ping (2016)
Solid oxide fuel cell (SOFC) is an electrochemical device which converts chemical energy of a fuel into electricity and is emerging due to its high conversion efficiency and minimal environmental impact. In this study, the main objectives are to improve the formulation of electrolyte in the fabrication of electrolyte-supported SOFC using aqueous-based tape casting and to optimize the performance of SOFC. Button cells instead of large area cell were prepared first as they allowed quick screening of testing criteria for data collection. Fuel cell electrolyte was fabricated using aqueous-based tape casting followed by sintering process. Experimental results showed that scandium stabilized zirconia (SSZ) electrolyte had the greatest conductivity with values of 0.133, 0.101, 0.069, 0.041 and 0.020 S/cm at operating temperatures of 850 to 650°C at 50°C intervals. La0.6Sr0.4Co0.2Fe0.8O3+d (LSCF) was screen printed onto both sides of electrolyte and its electrochemical performance was tested. At operating temperature of 800°C, the lowest ohmic resistance and polarization resistance of LSCF was 0.47 and 0.45 Ω cm^2 respectively. Next, electrolyte-supported SOFC button cell was prepared with SSZ electrolyte, La0.75Sr0.25Cr0.5Mn0.5O3-δ and ceria gadolinium oxide (LSCM + CGO) as fuel electrode and LSCF as air electrode. Button cells with different fuel electrode sintering temperatures were tested to obtain the electrochemical impedance spectrums as well as current-voltage (I-V) and current-power density (I-P) curves. At operating temperature of 800°C, the highest peak power density was achieved by button cell with fuel electrode sintering temperature of 1300°C, followed by those at 1400, 1200, 1100 and 1000°C with the values of 202, 165, 137, 116 and 93 mW/cm^2 respectively. In addition, the lowest ohmic resistance was attained by button cell with fuel electrode sintering temperature of 1300°C, followed by those at 1200, 1400, 1100 and 1000°C with the values of 0.31, 0.34, 0.35, 0.49 and 0.81 Ω cm^2 respectively. Button cell with fuel electrode sintering temperature of 1300°C also has the lowest polarization resistance, followed by those at 1400, 1200, 1100 and 1000°C with the values of 0.62, 0.70, 1.08, 1.55 and 1.92 Ω cm^2 respectively.